Critical Stylistic Analysis of Naming and Describing of Selected Media News - Adai, Salih Mahdi; Kareem, Thamir Muhammad (Randwick International of Education and Linguistics Science Journal, 2025)
This study employs Jeffries’ (2010) critical stylistics framework, focusing on the linguistic tool of "naming and describing," to analyze how media outlets construct ideological narratives in their coverage of sensitive political conflicts, specifically those involving Palestine and Lebanon. By examining selected news samples from two prominent Arabic-language channels, Al Jazeera and Al Arabiya, which hold contrasting political alignments, the research investigates how lexical and descriptive choices reflect their ideological orientations. The findings reveal how media language subtly shapes public opinion and constructs social realities, highlighting the role of linguistic strategies in framing political events.